Clinical, hematological, and flow cytometric correlation of acute leukemia in children: a study from a tertiary pediatric care facility in Hyderabad, Telangana - Munirathinam, Priyadarsini; Sandanala, Srikanth; Nanditha, Addagatla; Madheswaran, Madhan Kumar (International Journal of Contemporary Pediatrics, 2025)
Background: Acute leukemia is the most common malignancy in children, accounting for approximately 30-40% of all childhood cancers. In India, pediatric acute leukemia presents a significant public health challenge due to its rising incidence, diagnostic delays, and variable access to specialized care. clinical features, hematological parameters (including smear), flow cytometry are essential for diagnosis, risk stratification and prognosis of the disease. Methods: The study was conducted on 77 patients’ children aged 1 month to 12 years who were diagnosed with acute leukemia. Results: The majority of participants were between 1 to 5 years (42.9%) with definite male predominance (57.1%). Common clinical features were fever (87%), Bleeding manifestations (40.3%), joint pain (15.6%). Splenomegaly and hepatosplenomegaly were observed in 29.9% and 48.1% of the participants. B-cell acute lymphoblastic leukaemia (ALL) was most common (70.1%). Among acute myeloid leukemia subtypes, AML M2 was predominant, and T-cell ALL was relatively rare (3.9%). On flow cytometry analysis of B-ALL, B-cell markers were exclusively expressed and CD34 was positive in 44.2% of the cases. CD10, CD19, and CD79 were exclusively expressed in B-ALL, while MPO, CD13, CD33, and CD117 were strongly associated with AML. T-ALL was characterized by the expression of CD3, CD2, and CD5. Distinct expression patterns of markers such as CD41 and CD61 observed in AML M7 subtype. Conclusions: Overall, the integration of clinical, hematological, and flow cytometric findings will enable accurate diagnosis and characterization of pediatric leukemia and in further management.